Contrasting responses in the growth and energy utilization properties of sympatric Populus and Salix to different altitudes: implications for sexual dimorphism in Salicaceae. Issue 1 (13th July 2016) - Lei, Yanbao; Chen, Ke; Jiang, Hao; Yu, Lei; Duan, Baoli
Abstract : An interesting ecological and evolutionary puzzle arises from the observations of male‐biased sex ratios in genus Populus, whereas in the taxonomically related Salix, females are generally more dominant. In the present study, we combined results from a field investigation into the sex ratios of the Salicaceous species along an altitudinal gradient on Gongga Mountain, and a pot experiment by monitoring growth and energy utilization properties to elucidate the mechanisms governing sexual dimorphism. At middle altitudes 2000 and 2300 m, the sex ratios were consistent with a 1:1 equilibrium in sympatric Populus purdomii and Salix magnifica . However, at the lower and higher ends of the altitudinal gradient, skewed sex ratios were observed. For example, the male:female ratios were 1.33 and 2.36 in P. purdomii at 1700 and 2600 m respectively; for S. magnifica the ratio was 0.62 at 2600 m. At 2300 m, the pot‐grown seedlings of both species exhibited the highest biomass accumulation and total leaf area, simultaneously with the balanced sex ratios in the field. At 3300 m, the specific leaf area in male P. purdomii was 23.9% higher than that of females, which may be the morphological cause for the observed 19.3% higher nitrogen allocation to Rubisco, and 20.6% lower allocation to cell walls. As such, male P. purdomii showed a 32.9% higher foliar photosynthetic capacity, concomitant with a 12.0% lower construction cost. These properties resulted in higher photosynthetic nitrogen‐ and energy‐use efficiencies, and shorter payback time (24.4 vs 40.1 days), the time span that a leaf must photosynthesize to amortize the carbon investment. Our results thus suggested that male P. purdomii evolved a quicker energy‐return strategy. Consequently, these superior energy gain‐cost related traits and the higher total leaf area contributed to the higher growth rate and tolerance in stress‐prone environments, which might, in part, shed new light on the male‐biased sex ratios in Populus . However, no significant sexual difference was observed in S. magnifica for all the above parameters, thereby implying that the female‐biased sex ratios in Salix cannot be explained in terms of the energy‐use properties studied here.